2012
DOI: 10.1161/atvbaha.111.238063
|View full text |Cite
|
Sign up to set email alerts
|

The β-Chain of Cell Surface F 0 F 1 ATPase Modulates ApoA-I and HDL Transcytosis Through Aortic Endothelial Cells

Abstract: Objective-Both HDLs and their major protein constituent apolipoprotein A-I (apoA-I) are transported through aortic endothelial cells. The knock-down of the ATP-binding cassette transporters A1 (ABCA1), G1 (ABCG1), and of the scavenger receptor-BI (SR-BI) diminishes but does not completely block the transport of apoA-I or HDL, so that other receptors appear to be involved. The ectopic ␤-chain of F 0 F 1 ATPase has been previously characterized as an apoA-I receptor, triggering HDL internalization in hepatocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
104
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(105 citation statements)
references
References 43 publications
0
104
1
Order By: Relevance
“…Conversely, siRNA-mediated gene silencing experiments revealed that the cell surface binding and transport of HDLs through aortic endothelial cells are highly dependent on SR-BI and ABCG1, but not on ABCA1 (Rohrer et al 2009). Subsequent research has demonstrated expression of the ectopic β-chain of F0F1 ATPase (β-ATPase) on the endothelial cell surface (Cavelier et al 2012). The results of this study further suggest that the binding of lipid-free apoA-I to endothelial cell surface β-ATPase facilitates the uptake and transport of lipidated apoA-I and mature HDLs by enhancing β-ATPase-mediated hydrolysis of extracellular ATP into ADP and inducing consecutive activation of the purinergic P2Y12 receptor (Cavelier et al 2012).…”
Section: Transendothelial Hdl Transportmentioning
confidence: 59%
See 1 more Smart Citation
“…Conversely, siRNA-mediated gene silencing experiments revealed that the cell surface binding and transport of HDLs through aortic endothelial cells are highly dependent on SR-BI and ABCG1, but not on ABCA1 (Rohrer et al 2009). Subsequent research has demonstrated expression of the ectopic β-chain of F0F1 ATPase (β-ATPase) on the endothelial cell surface (Cavelier et al 2012). The results of this study further suggest that the binding of lipid-free apoA-I to endothelial cell surface β-ATPase facilitates the uptake and transport of lipidated apoA-I and mature HDLs by enhancing β-ATPase-mediated hydrolysis of extracellular ATP into ADP and inducing consecutive activation of the purinergic P2Y12 receptor (Cavelier et al 2012).…”
Section: Transendothelial Hdl Transportmentioning
confidence: 59%
“…Subsequent research has demonstrated expression of the ectopic β-chain of F0F1 ATPase (β-ATPase) on the endothelial cell surface (Cavelier et al 2012). The results of this study further suggest that the binding of lipid-free apoA-I to endothelial cell surface β-ATPase facilitates the uptake and transport of lipidated apoA-I and mature HDLs by enhancing β-ATPase-mediated hydrolysis of extracellular ATP into ADP and inducing consecutive activation of the purinergic P2Y12 receptor (Cavelier et al 2012). More recently, transendothelial transport of HDL particles was found to be modulated by endothelial lipase both through its enzymatic lipolytic activity and its ability to bridge the binding of lipoproteins to the endothelial surface (Robert et al 2013).…”
Section: Transendothelial Hdl Transportmentioning
confidence: 59%
“…A subsequent study demonstrated a major role of cytoskeleton reorganization in F(1)-ATPase/P2Y(13)-dependent HDL endocytosis under the control of the small GTPase RhoA and its effector ROCK I (Malaval et al 2009). Others showed that binding of HDL to this receptor triggers the generation of ADP, which via the activation of the purinergic receptor P2Y13 stimulates the uptake and transport of HDL and initially lipid-free apoA-I by endothelial cells (Cavelier et al 2012). So far, there is no genetic support for the involvement of beta-chain of ATP synthase and/or P2Y(13), but even mild mutations could have in the case of ATPB5 lethal consequences.…”
Section: Beta-chain Of Atp Synthasementioning
confidence: 99%
“…In this as-yet-poorlyunderstood pathway, a high-affinity interaction of apoA-I with ectopic F0F1-ATPase leads to the formation of ADP, which activates purinergic receptors to induce the uptake of HDL by an as-yet-unidentified low-affinity HDL receptor. [34][35][36] The 2 better-characterized pathways mediate the removal of lipids from HDL independently of its protein moiety: CETP exchanges triglycerides of apoB-containing lipoproteins for cholesteryl esters of HDL, which are ultimately eliminated via the LDL receptor pathway, and SR-BI mediates the selective uptake of HDL lipids into the liver and steroidogenic organs. 11,33 The removal of cholesteryl esters by CETP and SR-BI, as well as the lipolysis of triglycerides and phospholipids by hepatic lipase and endothelial lipase, respectively, leads to the conversion of HDL 2 into HDL 3 as well as the generation of pre-β 1 -HDL.…”
mentioning
confidence: 99%